Anatomy of the Mental Foramen: Relationship among Different Metrical Parameters for Accurate Localization - Michaela Cellina; Carlo Martinenghi; Sandro De Nardi; Andrea Palamenghi; Maurizio Cè; Chiarella Sforza; Annalisa Cappella; Daniele Gibelli (Applied Sciences, 2023)
Purpose: The mental foramen (MF) is important in dental surgery procedures for preventing possible iatrogenic lesions and for anesthetic procedures. This paper aims at expanding knowledge on the metrical characteristics that are useful for the correct anatomical assessment of the MF. Materials and Methods: On 100 CBCT scans (50 males and 50 females), height, width, depth, linear distance from the inferior and superior mandibular edge and position according to teeth and dental apices were analyzed. Differences according to sex and the side for each metrical measurement and for teeth and dental apices were assessed through a two-way ANOVA test and Chi-square test, respectively. Pearson’s test and a one-way ANOVA test were used to test correlations among the chosen parameters (p < 0.01). Results: The depth and distance from the inferior and superior mandibular edges showed sexual dimorphism (p < 0.01). Height and width were positively related, as well as depth and distance from the inferior mandibular edge in females (p < 0.01). Conclusions: Novel data about the anatomical position of the mental foramen are described, which are useful for the management of surgical procedures.